PWE-066 Impact of Right Colon Retroflexion on Adenoma Detection Rate. (4th June 2013) - Widlak, M; Muhammad, H; Smith, M; Shetty, S; Cooper, S C; Silva, S De; Fisher, N; Ishaq, S
Abstract : Introduction: Colonoscopy is less effective in visualising the right colon compared with the rest of the colon and small adenomas are frequently missed during routine procedures. The aim of this study was to determine whether retroflexion in the right colon would improve adenoma detection rate. Methods: We carried out a prospective pilot study on a total of 37 adults who underwent elective diagnostic colonoscopy with a EC3490 TFi (Pentax retro-view) colonoscope between October 2012 and January 2013. A careful colonic examination to the caecum in the forward view was performed. The colonoscope was then retroflexed in the right colon to identify any additional adenomas. Success rate of retroflexion, adenoma detection rate in forward-viewing as well as in retroflexion were assessed along with comfort scoring and incidence of adverse events. Results: Study population of 37 patients, mean age 62 yrs, F: M ratio 1:0.8.Retroflexion in the right colon was successful in 34 patients (92%), with looping on insertion the cause of the failures. On forward viewing 28 polyps were identified, of which 11 adenomas were in the proximal colon. Retroflexion identified an additional 3 adenomas (all < 1cm), improving the overall adenoma detection rate by 9%. 81% of patients did not experience any discomfort (comfort score 0) during the procedure. Apart from one minor post-polypectomy haemorrhage no adverse events were recorded. Conclusion: This preliminary data suggests that right colon retroflexion may improve the adenoma detection rate of colonoscopy. Although the procedure is feasible, safe and easy to carry out, further high power studies are needed to establish whether retroflexion should be incorporated into standard colonoscopy technique. Disclosure of Interest: None Declared.